Cervical dilatation in parturient receiving neuraxial analgesia: Comparison of epidural analgesia alone with combined spinal epidural analgesia - Geetha C Rajappa; Tejesh C Anandaswamy; Thejaswini J Pattadi; Asha Swarup (Journal of Obstetric Anaesthesia and Critical Care, 2017)
Background: Both epidural analgesia and combined spinal epidural analgesia (CSEA) are employed for pain relief during labor because they provide reliable analgesia compared to other modalities. Studies are equivocal with respect to their effect on the rate of cervical dilatation, duration of labor, and labor outcome. The primary outcome of the present study was to compare the effect of epidural analgesia alone with CSEA with respect to the rate of cervical dilatation. Materials and Methods: One hundred and twenty parturients with an initial cervical dilatation of <4 cm were randomized to receive CSEA or epidural analgesia alone for pain relief during labor. The rate of cervical dilatation, onset of effective analgesia, number of epidural top-ups requested, labor outcome, and the quality of analgesia was assessed in both the study groups. Statistical Analysis: Mann–Whitney and Chi-square tests were performed where applicable to compare the data between the two groups. Results: The results of the study showed that the rate of cervical dilatation was rapid with CSEA compared to epidural analgesia alone [median (interquartile range) 2 (1.2,3) v/s 1.16 (1,2)]. The onset of analgesia was earlier with combined spinal epidural (CSE v/s EA, 3.7 ± 1.3 min v/s 23.8 ± 5.8 min). Labor outcome and quality of analgesia was similar between the two groups. The incidence of pruritus was higher with CSEA than with epidural analgesia alone. Conclusion: CSEA is associated with more rapid cervical dilatation and shorter duration of first stage of labor when compared with epidural analgesia alone.